Constrained contexts, resilient teachers: instructional adaptation, student engagement, and professional well-being - Donnie M. Tulud; Mirasol O. Verona; Elangbai B. Dimasingkil; Estella B. Barbosa; Lloyd Anton Von M. Colita; Marlon T. Salvador; Ronel A. Naringahon; Nora B. Bolences; Edna Luz T. De Guzman; Orfelina M. Ajero; Ruben L. Tagare, Jr. (International Journal of Evaluation and Research in Education (IJERE), 2026)
Filipino secondary teachers face significant challenges in constrained educational contexts, including limited resources, rigid curricula, and systemic pressures that affect instructional quality and student engagement. This study explored how teachers navigate these constraints, adapt instruction, and maintain professional well-being. A qualitative descriptive design was employed, involving fifteen purposively selected teachers who met criteria of active teaching and willingness to participate. Data were collected using validated open-ended guide questions and analyzed through Colaizzi’s framework to identify recurring patterns and themes. Findings revealed five interconnected themes: normalization of instructional compromise, limited opportunities for pedagogical innovation, teacher morale vulnerability, student compliance over genuine engagement, and resilience-driven teaching culture. These results indicate that systemic constraints shape instructional practices, often prioritizing syllabus completion over mastery, and influence student engagement through extrinsic motivation. Despite these challenges, teachers exhibited resilience through adaptability, improvisation, and commitment, sustaining both instructional continuity and personal well-being. The study underscores the critical role of teacher agency, morale, and resilience in navigating structural limitations, offering insights into professional adaptation and the complex dynamics of teaching in constrained educational environments.